A well‐preserved Eemian incised‐valley fill in the southern North Sea Basin, Belgian Continental Shelf ‐ Coastal Plain: Implications for northwest European landscape evolution. Issue 9 (13th March 2018) - De Clercq, M.; Missiaen, T.; Wallinga, J.; Zurita Hurtado, O.; Versendaal, A.; Mathys, M.; De Batist, M.
Abstract: This paper demonstrates that the Belgian Continental Shelf and coastal plain occupy a key position between the depositional North Sea Basin and the erosional area of the Dover Strait as it is an area where erosional landforms and fragmented sedimentary sequences provide new evidence on northwest European landscape evolution. The study area hosts 20–30 m thick penultimate to last glacial sand‐dominated sequences that are preserved within the buried palaeo‐Scheldt Valley. Here, we build on the results of previous seismo‐ and lithostratigraphical studies, and present new evidence from biostratigraphical analysis, OSL dating and depth‐converted structure maps, together revealing a complex history of deposition and landscape evolution controlled by climate change, sea‐level fluctuations and glacio‐isostasy. This study presents strong new supportive evidence on the development of the incised palaeo‐Scheldt Valley landform that became established towards the end of the penultimate glacial period (MIS 6; Saalian) as a result of glacio‐isostatic forebulge updoming, proglacial lake drainage and subsequent collapse of a forebulge between East Anglia and Belgium following ice‐sheet growth, disintegration and retreat in areas to the north. The majority of the incised‐valley fill is of estuarine to shallow marine depositional context deposited during the transgression and high‐stand of the last interglacial (MIS 5e: Eemian). A thin upper part of the valley fill consists of last glacial (MIS 5d‐2: Weichselian) fluvial sediments that show a gradual decrease and retreat of fluvial activity to inland, upstream reaches of the valley system until finally the valley ceases to exist as the combined result of climate‐driven aeolian activity and possibly also glacio‐isostatic adjustment. Thus, strong contrasts exist between the palaeo‐Scheldt Valley and estuary systems of the penultimate glacial maximum to Last Interglacial (Saalian, Eemian), the beginning of the Last Glacial (Weichselian Early Glacial and Early‐Middle Pleniglacial), and the Last Glacial Maximum to Holocene. Copyright © 2018 John Wiley & Sons, Ltd. Abstract : A geogenetic analysis of the palaeo‐Scheldt incised‐valley system in northwest Belgium and its continental shelf: how an erosional shelf area provides new insights to the late Middle Pleistocene and younger landscape evolution of the southern North Sea Basin.